ANALISIS KESALAHAN SINTAKSIS PADA KALIMAT “ADJECTIVE CLAUSE “ MAHASISWA SEMESTER V PROGRAM STUDI BAHASA INGGRIS STBA JIA BEKASI - Elsan Arvian (STBA JIA Press, 2020)
Indonesian students often face difficulties when they have to write in English. Especially, they are asked to form standard and acceptable sentence structures. This study aims to describe the types of syntactic errors contained in the fifth semester student clause of the English study program, find the most dominant type of error and describe the factors that might be the cause of the error. Data was collected from the writing of semester V students of the English study program 2018-2019. This research uses descriptive analysis method. Data were analyzed by classifying errors using linguistic categories Language error category (West, 2008). The researcher used Corder ’s theory (1982) for searching the causes of syntactic errors made by the students. These theories ultimately strengthen the researcher's hypothesis that the cause of syntactic errors made by students is the interlingual factor namely the first language interference in the target language. Based on the findings, the most numerous and dominant errors are verbs (verb) not in accordance with the subject.